2022
DOI: 10.1001/jamaophthalmol.2022.0671
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Visual Field Change in Patients With Glaucoma and Healthy Individuals

Abstract: IMPORTANCEEstimating the rate of glaucomatous visual field change provides practical assessment of disease progression and has implications for management decisions.OBJECTIVE To assess the rates of visual field change in patients receiving treatment for glaucoma compared with healthy individuals over an extensive follow-up period and to quantify the impact of important covariates for these rates. DESIGN, SETTING, AND PARTICIPANTSThis prospective longitudinal cohort study was conducted in a hospital-based setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Several clinical trials and longitudinal studies have identified age as an independent risk factor for progression in glaucoma. (11,27,52,53) However, when dealing with individual patients, the consensus is not to treat older individuals more aggressively than younger ones but, in fact, to do the opposite. This paradoxical recommendation makes sense when life expectancy is taken into account: for instance, consider two newly diagnosed male patients with moderate visual field defect and IOPs of 24mmHg, one being 50-year-old and the other being 85-year-old.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials and longitudinal studies have identified age as an independent risk factor for progression in glaucoma. (11,27,52,53) However, when dealing with individual patients, the consensus is not to treat older individuals more aggressively than younger ones but, in fact, to do the opposite. This paradoxical recommendation makes sense when life expectancy is taken into account: for instance, consider two newly diagnosed male patients with moderate visual field defect and IOPs of 24mmHg, one being 50-year-old and the other being 85-year-old.…”
Section: Agementioning
confidence: 99%
“…This study confirms that in patients with glaucoma who are actively managed with regular visits, progression tend to be slow and not lead to significant visual disability in most cases, even after 25 years of follow-up. (52) Some practical recommendations regarding visual field monitoring in glaucoma:…”
Section: Practical Recommendations and Tolerable Rates Of Visual Fiel...mentioning
confidence: 99%
“…To the Editor We read with interest the work by Giammaria et al We do have some observations on the study and some questions to help clarify our understanding of the results:…”
mentioning
confidence: 99%
“…Such a long observation period is associated with much attrition, which implies a highly selective follow-up. By the end of the study, were the 40 or so cases more motivated and more compliant with treatment than most patients with glaucoma?…”
mentioning
confidence: 99%
See 1 more Smart Citation